A corpus-based view on the (aspectual-)semantics of Modern English nominalizations. (May 2019) - Fonteyn, Lauren
Abstract: In this response article, I will challenge some of the claims presented by Iordăchioaia & Werner by suggesting that English ing- nominals were not entirely prevented from completing the 'cycle of categorial shift', and questioning the actual impact of the competition with Romance derived nominals on the development of ing- nominals with event denotation (i.e. nominal gerunds). The response is based on a detailed corpus-based analysis of Penn corpora of Modern English (PPCEME & PPCMBE, time span: 1500–1920), and consists of three components: (i) a summary of a recent study byFonteyn and Hartmann (2016), in which it is argued that many nominal ing -forms did complete the full nominalization cycle from eventive to concrete object meanings, (ii) a more fine-grained aspectual-semantic analysis of eventive ing -nominals (or nominal gerunds), and (iii) a detailed comparison between ing -nominals and Romance derived nominals in -age, -al, -ance, -ion, and - ment, mapping out the areas of overlap and the effect of competition on the semantic development of the different nominalization strategies. In the conclusion, it is argued that the intriguingly versatile usage profile of English ing- nominals in Modern English is shaped by a constant diachronic interaction with their neighbouring constructions. Highlights: The semantics of ing -nominals are not specialised in process meaning but appear to be intriguingly versatile: they occur with non-eventive meanings (Section3.1 ) and are also quite commonly used to express result-oriented (telic) as well as processual (atelic) situations (Section3.2 ). English ing- nominalssimultaneously have become more delineated and non-eventive (like German ung -nominals) while also retaining their ties to their processual uses (unlike German ung -nominals). The data analysis in Section3.3 indicates that there is only a relatively small amount of overlap between English ing- nominals and Romance derived nominals, suggesting that the actual area of competition between these two nominalization types was limited. The analysis does not provide any clear support for the hypothesis that Romance derived nominals caused a specialization of ing- nominals to processual semantics.